Muscle Asymmetries in the Lower Limbs of Male Soccer Players: Preliminary Findings on the Association between Countermovement Jump and Tensiomyography - Alex Buoite Stella; Annalisa Galimi; Miriam Martini; Luca Di Lenarda; Luigi Murena; Manuela Deodato (MDPI AG, 2022)
Strength and power asymmetries have been observed in different sports, including soccer. Such asymmetries, as well as the bilateral deficit (BLD), can be assessed during different tasks, static or dynamic, and with different methods and devices, in order to detect the possible different aspects, as well as the association with physical performance and injuries. The aim of this study was to investigate the association between muscle asymmetries and BLD during a countermovement jump (CMJ), and tensiomyography (TMG) parameters and asymmetries, in the lower limbs of male soccer players. A total of 23 male soccer players (18 ± 4 years) were recruited. Bilateral and unilateral CMJs were performed, and peak power (W) and height (cm) were obtained. TMG was performed on different muscles of the lower limbs, and lateral and functional symmetries were obtained. Playing position and history of injuries were collected. CMJ inter-limb symmetry was found to significantly correlate with biceps femoris (r = 0.574, p = 0.004) and soleus (r = 0.437, p = 0.037) lateral symmetry. Players in central roles presented significantly worse functional symmetry scores of the knee than defense players (−17.5%, 95% CI −31.2-−3.9; p = 0.10). Participants reporting a history of injury at the ankle were characterized by significantly lower functional symmetry in both the dominant (43%, 39.5-48.0 vs. 74.5%, 46.5-89.3, p = 0.019) and non-dominant (45%, 42.5-46.0 vs. 81.0%, 45.8-90.3, p = 0.024) ankle. Findings from this preliminary study suggest an association between lower-limb muscle asymmetries during a dynamic task, such as jumping, and muscle contractile properties evaluated with TMG; moreover, functional asymmetries may be present after ankle injuries. Future studies in larger samples should evaluate the presence of such asymmetries as predictors or characteristics of different muscular and joint injuries.